Negatif poisson oranına sahip (Auxetic) malzemeler ve uygulama alanları - (:unkn) unknown (My University, 2010)
Akıllı malzemelere olan ilgi ve ihtiyacın her gecen gün artmasıyla yeni ve çok fonksiyonlu malzemeler tasarlanıp üretilmektedir. Akıllı malzeme üretimi ya yeni bir ürün geliştirilmesiyle ya da geleneksel malzemeye ek özellikler kazandırılmasıyla oluşur. Bu çalışmada geleneksel malzemelerin negatif Poisson oranına sahip olmaları durumunda ne gibi ek özellikler kazanacağı ve kullanımdaki artı özellikleri incelenmiştir. Çevremizde gördüğümüz malzemelerin büyük çoğunluğu pozitif Poisson oranına sahipken sınırlı sayıda ki malzeme negatif Poisson oranına sahiptir.

The interest and demand of smart materials are increasing with each passing day. For this reason, many new functional materials are designed and fabricated. There are two methods for fabrication of smart materials. One of them is creating entirely new material, another is by adding novel properties to the traditional materials. The aim of this study is to give an idea about the negative Poisson ratio behaviour for new smart materials. Which features of materials can be enhanced with negative Poisson ratio? If we look around, we can see large majority of materials have positive Poisson ratio but there is some materials which have negative Poisson ratio.
Negative poisson ratio (Auxetic) materials and their applications